STRATEGY FOR UNDERSTANDING THE FUNDAMENTALS OF CELLULAR RESPIRATION THROUGH THE USE OF ELECTRONIC DEVICES - Jerez-Jaimes, Javier Hernando; Narváez-Parra, Eliana Ximena (Innovaciencia, 2016)
Introduction: The development of strategies that involve the applicability of the concepts learned in everyday situations, constitutes a key tool to integrate the competences of to know with the to do competences. Some electronic devices used frequently in the job of the nurse to assess aspects of the health of the patients were tested like materials to support the teaching of the cellular respiration and mitochondrial activity. Methods: This project was developed with a group of 34 students, from the first semester of Nursing Faculty of the Universidad Cooperativa de Colombia, they were divided into eight working groups with roles assigned to evaluate in an indirect form the processes of cellular respiration and its interrelationship with other biological systems through the techniques of pulse oximetry, glucometry and infrared thermometry, during three moments (rest, exercise and relaxation) in the test of step. Results and Discussion: The students raised scientific questions and established hypothesis before making the measurements of the variables. The students showed a good acceptance by the work outside the classroom. Using the evaluation rubric we found that students failed in the confrontation of the hypothesis due to the inability to identify and graphing variables, similarly showed minimal competences to correlate and integrate the information obtained experimentally. Conclusions: Was developed, implemented and evaluated the proposed practice integrating and conceptualising the knowledge related to the cellular respiration and mitochondrial activity. The strategy presented allows to improve the learning of the students, it requires little investment, favors the short researches, but requires basic skills in scientific and critical thinking, in addition to earlier practices that introduce the student to the world of science. The students showed a greater performance in to do competences more than to know competences.